A combined technique for the pretreatment of ultra trace bisphenol A in environmental water based on magnetic matrix solid phase extraction assisted dispersive liquid–liquid microextraction. Issue 24 (17th November 2015) - Diao, Chunpeng; Yang, Xiao; Sun, Ailing; Liu, Renmin
Abstract : Magnetic matrix solid phase dispersion (MMSPD) assisted dispersive liquid–liquid microextraction (DLLME) for the ultrasensitive determination of bisphenol A (BPA) in environmental water was developed with HPLC-FLU detection. Abstract : Magnetic matrix solid phase dispersion (MMSPD) assisted dispersive liquid–liquid microextraction (DLLME) for the ultrasensitive determination of bisphenol A (BPA) in environmental water was developed with high performance liquid chromatography-fluorescence (HPLC-FLU) detection. Microparticles of magnetic activated carbon (MAC) were synthesized and used to conduct the MMSPD procedure. The specific surface area of the MAC was 287 m 2 g −1, and the saturation magnetization of the MAC supported by Fe3 O4 nanoparticles was up to 20.7 emu g −1 . BPA in water was adsorbed by microparticles of MAC and then transferred into the elution solvent by elution. The DLLME procedure was assisted by the elution solvent acting as the dispersive solvent. BPA in the elute solvent of the MMSPD procedure was concentrated into the trace volume extraction solvent of the DLLME procedure. A sufficiently low limit of detection (LOD) of 0.002 μg L −1 for the determination of BPA in environmental water was obtained. Good linearity was obtained throughout the concentration range of 0.006 to 5.0 μg L −1 with a correlation coefficient ( R 2 ) of 0.9991. The relative standard deviation (RSD) was 6.2%. The relative recoveries ranged from 86.6 to 106.3% for the spiked real water samples. The results showed that the MMSPD assisted DLLME technique is highly sensitive and reliable for the determination of trace BPA in environmental water.